A formação continuada de professores/as e a construção do currículo da educação física da rede municipal de Sobral - Lopes, Francisco Junielison Correia (2024)
This research aims to understand the influence of continuous teacher training on the construction of the Physical Education curriculum in the municipal education network of Sobral, Ceará. The justification for this study lies in the need to understand how continuous training can contribute to the improvement of pedagogical practices and overcome the challenges faced by teachers in the ongoing process of constructing the Physical Education curriculum. The municipality of Sobral began the discussion on a unified curriculum in 2001, seeking to standardize teaching across all subjects in the municipal network. This research seeks to understand continuous training from the perspective of curriculum construction, evaluating the challenges and obstacles faced by teachers and analyzing their perceptions of the training process itself. This is a qualitative research with a descriptive objective and an inductive method. The study was conducted from October 2023 to April 2024 through interviews with Physical Education teachers in the municipal network. A semi-structured research methodology was used, applied both in person and online via Google Meet. The collected information was categorized and analyzed according to Laurence Bardin's content analysis method. Document analysis was also conducted, based on the Unified Annual Course Plan, a document that precedes the construction of curricula in the municipality. Based on this research, an educational product titled “Action Plan for the Collaborative Construction of a Physical Education Curriculum” was developed, suggesting topics and subjects to be addressed in school Physical Education. The main results highlight many teachers' desire for a curriculum developed with the co-participation of all stakeholders and that it can be periodically reassessed, given the need to include regional issues and other socially relevant topics. There was also some dissatisfaction among teachers with the National Common Core Curriculum (BNCC), as some interviewees believe it may restrict certain pedagogical proposals. In summary, the main findings based on the specific objectives are: (1) recognition of the importance of continuous training for improving work and unifying network operations; (2) appreciation of the exchange of experiences; (3) criticism regarding the format of the training sessions, as well as suggestions for improvement, mainly concerning the need to value teachers who are currently teaching, rather than external teachers; (4) the perception that the curriculum should be flexible and built collectively; (5) dissatisfaction with the BNCC for often restricting current curriculum proposals and the loss of autonomy.